Mais um número da REF: entre a esperança e os sobressaltos do processo eleitoral - Simões, Luzinete; Ramos, Tânia Regina; Lago, Mara; Scheibe Wolff, Cristina (Revista Estudos Feministas, 2023)
Editorial